2020
DOI: 10.1016/j.jaip.2020.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Fitness in the Age of Social Distancing During the COVID-19 Pandemic

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
143
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(176 citation statements)
references
References 3 publications
3
143
0
14
Order By: Relevance
“…Therefore, quitting smoking is recommended, especially for those with underlying diseases [20]. The nding that physical activity was associated with a higher well-being score resonates with previous studies which found that physical activity improves mental well-being, in addition to reducing the risk of acute respiratory distress syndrome which is a major cause of death in COVID-19 patients [21].…”
Section: Discussionsupporting
confidence: 59%
“…Therefore, quitting smoking is recommended, especially for those with underlying diseases [20]. The nding that physical activity was associated with a higher well-being score resonates with previous studies which found that physical activity improves mental well-being, in addition to reducing the risk of acute respiratory distress syndrome which is a major cause of death in COVID-19 patients [21].…”
Section: Discussionsupporting
confidence: 59%
“…The unique importance of physical activity and of restricting sedentary behaviors cannot be overstated, considering their beneficial effects on health in general, and also on specific elements related to the COVID-19 pandemic, such as modulation of the immune system [ 51 ]. Therefore, the WHO and many other professional societies recommend the adoption of specific exercise programs and daily strategies including home-based exercise programs to maintain a physically active lifestyle during the pandemic [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“… 4 Other online classes, including cycling, yoga, and dance classes, can be broadcast by means of video conferences to allow clients to exercise in a safe and comfort environment. 4 For those who insist on working out outdoors, personalized training videos focusing on improving the form and posture can be taught through virtual classes, thereby modifying the exercise form of the clients and reducing future injury risks when the quarantine policy is lifted. Overall, the goal is to provide patients with optimal choices that best suit their personal interests and individualized goals.…”
Section: Exercise/rehabilitationmentioning
confidence: 99%
“…As healthcare providers, we must shed light on this ongoing trend of changing lifestyles and physical activity properties and provide our patients with comprehensive strategies to maintain fitness levels during the quarantine. 4 …”
Section: Introductionmentioning
confidence: 99%